2015
DOI: 10.1111/cei.12570
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor binding affinity governs the functional profile of cancer-specific CD8+ T cells

Abstract: Antigen-specific T cell receptor (TCR) gene transfer via patient-derived T cells is an attractive approach to cancer therapy, with the potential to circumvent immune regulatory networks. However, high-affinity tumour-specific TCR clonotypes are typically deleted from the available repertoire during thymic selection because the vast majority of targeted epitopes are derived from autologous proteins. This process places intrinsic constraints on the efficacy of T cell-based cancer vaccines and therapeutic strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 79 publications
4
114
1
Order By: Relevance
“…Studies performed over the last two decades have focused on empirically mapping the relationship between pMHC affinity and T-cell activation (5,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). A number of studies have reported an optimal pMHC affinity for T-cell activation, but other studies have failed to observe the optimum.…”
mentioning
confidence: 99%
“…Studies performed over the last two decades have focused on empirically mapping the relationship between pMHC affinity and T-cell activation (5,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). A number of studies have reported an optimal pMHC affinity for T-cell activation, but other studies have failed to observe the optimum.…”
mentioning
confidence: 99%
“…Efficient triggering of T-cell responses critically depends on the strength of TCR-mediated antigen recognition, namely it has been shown that strong binding to pMHC confers superior effector function than weak interactions (2)(3)(4)(5)(6)(7). This is of particular interest for immunotherapy based on adoptive T-cell transfer, aiming to convey immune reactivity against tumorassociated antigens, for which endogenous T-cell responses are usually weak.…”
Section: Introductionmentioning
confidence: 99%
“…Use of TCRs with super-enhanced affinities (K D < 1 nM) in this way is not recommended as these receptors are usually selfreactive. 59 Nevertheless, the phage enhancement process allows generation of TCRs with a whole range of affinities that can be optimized via a rigorous preclinical evaluation process. 59 High-affinity tumor-specific TCR clonotypes are often deleted from the repertoire as most targeted cancer epitopes are derived from self-proteins.…”
Section: Preclinical Activitymentioning
confidence: 99%
“…59 Nevertheless, the phage enhancement process allows generation of TCRs with a whole range of affinities that can be optimized via a rigorous preclinical evaluation process. 59 High-affinity tumor-specific TCR clonotypes are often deleted from the repertoire as most targeted cancer epitopes are derived from self-proteins. Indeed, there is a wide affinity gap between TCRs that target pathogenderived epitopes and those that target self-epitopes.…”
Section: Preclinical Activitymentioning
confidence: 99%
See 1 more Smart Citation